Multi-scale characterization of bamboo bonding interfaces with phenol-formaldehyde resin of different molecular weight to study the bonding mechanism. Issue 162 (15th January 2020) - Huang, Yuxiang; Lin, Qiuqin; Yang, Chan; Bian, Guomin; Zhang, Yahui; Yu, Wenji
Abstract : Understanding the bonding mechanism of the interfacial region between bamboo and adhesives is essential for accelerating the development of improved adhesives for advanced bamboo-based materials. In this study, Br-labelled phenol-formaldehyde (PF) resins with four different molecular weights (MWs) were used to make bamboo–adhesive interfaces for tracing the adhesives in bamboo. Ultra-depth-of-field microscopy and scanning electron microscopy in conjunction with energy dispersion spectrometry were used to access the distribution and penetration of resin in the bamboo polymer. Fourier transform infrared images and solid-state cross-polarization/magic angle spinning nuclear magnetic resonance spectra were used to access the molecular-scale interactions between PF resins and bamboo cell walls. The results showed that the PF resins with high MW infiltrated into the lumina of damaged bamboo cells near the bondline to form glue nails, while those with low MW penetrated into the bamboo cell wall to form nanomechanical interlocking. Chemical bonds and secondary forces such as polar forces and hydrogen bonds were generated between bamboo and PF resin. Finally, the twice-adhesive dispensing method combining low-MW resins with high-MW resins was used to improve the bonding strength of the interface.